2016
DOI: 10.1038/srep37223
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1 is Required for Brown Adipose Tissue Recruitment and Metabolic Adaptation to Cold

Abstract: In response to cold, brown adipose tissue (BAT) increases its metabolic rate and expands its mass to produce heat required for survival, a process known as BAT recruitment. The mechanistic target of rapamycin complex 1 (mTORC1) controls metabolism, cell growth and proliferation, but its role in regulating BAT recruitment in response to chronic cold stimulation is unknown. Here, we show that cold activates mTORC1 in BAT, an effect that depends on the sympathetic nervous system. Adipocyte-specific mTORC1 loss in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
65
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 97 publications
(141 reference statements)
5
65
2
Order By: Relevance
“…7). We did not investigate the effect of rapamycin treatment on DNL during acute and chronic cold exposure because mTORC1 presents pleotropic effects, including mitochondrial biogenesis, oxidative metabolism, TCA, and nucleotide synthesis (33).…”
Section: Discussionmentioning
confidence: 99%
“…7). We did not investigate the effect of rapamycin treatment on DNL during acute and chronic cold exposure because mTORC1 presents pleotropic effects, including mitochondrial biogenesis, oxidative metabolism, TCA, and nucleotide synthesis (33).…”
Section: Discussionmentioning
confidence: 99%
“…Differently, DKO mice had reduction of BAT and iWAT mass and low levels of UCP1 and mitochondria-related proteins. Likewise, loss of Raptor in all mature adipocytes affects BAT expansion and adaptation to cold (25). Without functional mTORC1, Ucp1 expression in WAT cannot be induced by cold or AR3 agonists (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Adipocyte-specific KO of mTORC1 causes lipodystrophy, insulin resistance, and severe hepatic steatosis, but enhances energy expenditure and counteracts high-fat diet (HFD)-induced obesity (22)(23)(24). In BAT, loss of mTORC1 affects the BAT cold-adaptation and reduces BAT mass and lipid content (23,25), while activation of mTORC1 in WAT elevates Ucp1, PPAR coactivator 1 (Pgc1), and Ppar expression (26), suggesting a positive role of mTORC1 in regulating brown and beige adipogenesis. Adipose-specific mTORC2 ablation has little effect on fat cell size or fat mass, but leads to insulin resistance, affects glucose and lipid metabolism, and protects against HFD-induced obesity (19,20,27,28).…”
mentioning
confidence: 99%
“…Thus, in addition to its regulation by insulin, a well-known antagonist of PKA signaling, mTORC1 might also respond to catecholamines in adipocytes. Concurrently, other studies have shown that adrenergic stimulation may also stimulate mTORC2 and AKT signaling in certain settings suggesting that catecholamine-stimulated mTOR activity may be complex [72, 82]. Defining how PKA activates mTOR and what downstream mTOR-dependent pathways promote browning is an important future goal.…”
Section: Mtorc1 In Brown Adipocytes and The “Browning Of Wat”mentioning
confidence: 99%
“…Using Raptor Adipoq-Cre mice, one study looked carefully at how losing mTORC1 in all mature adipocytes affects BAT adaptation to cold [72]. In wild type mice, prolonged cold challenge significantly increases mTORC1 activity in BAT through sympathetic signaling and this correlates with increased BAT mass, mitochondrial biogenesis, and oxidative metabolism.…”
Section: Mtorc1 In Brown Adipocytes and The “Browning Of Wat”mentioning
confidence: 99%